Main competencies for sustainability in a Brazilian Public University - Garlet, Valéria; Beuron, Thiago Antonio; Balsan, Laércio André Gassen; Ávila, Lucas Veiga; Borges, Gustavo da Rosa; Madruga, Lucia Rejane da Rosa Gama (Revista de Administração da UFSM, 2019)
This study aimed to identify the competencies for sustainability of the public servers of a Brazilian public university in order to better understand the skills necessary to achieve sustainability in higher education institutions. A study carried out by documental research was conducted to identify how the sustainability is treated in the institution’s documents, in sequence a survey was conducted with 549 subjects. The findings reveal that the skills for sustainability are more focused on the individual level. It is necessary, therefore, that the university develops strategies and actions focused on the collective level. Institutionally, the university can promote and encourage training courses on education and sustainable management, development announcements that value stocks and interdisciplinary projects for sustainability and structuring of a sector that manage environmental issues at a strategic level.